PERANAN BANK SYARIAH INDONESIA DALAM MENINGKATKAN USAHA MIKRO KECIL (UMK) DI KOTA JAMBI (STUDI KASUS PADA BANK BSI KCP DR. SUTOMO JAMBI) - Dessy Anggraini; Yetti Suhartini (UIN Sulthan Thaha Saifuddin Jambi, 2024)
The results of initial observations that the author found are that what is happening now is that the financing distributed by Sharia Banks is not on target by providing financing to customers not for business development. This is reinforced by financing data which increases every year, but the number of micro and small businesses (UMK) in Jambi City has decreased. This is the problem that researchers want to study. With this Sharia Bank, it really helps customers in starting their business or vice versa. This research aims to determine the role of micro and small enterprises (UMK) in the existence of Bank BSI KCP Dr. Sutomo Jambi. This type of research is field research. This research collects data through interviews and documentation. This research is descriptive qualitative in nature and functions as a source of information about the role of Sharia Banks in improving micro and small enterprises (UMK). Based on the findings of interviews conducted with customers and the Head of BSI KCP Bank Sub-Branch, Dr. Sutomo Jambi, researchers can analyze how the existence of banks provides results and impacts on micro and small enterprises (UMK) in Jambi City. This can be seen from the increase in customer business after obtaining financing at the bank. Apart from that, customers also felt an increase in income, an increase in sales volume, and the addition of new employees to their business after financing at Bank BSI KCP Dr. Sutomo Jambi.